Hukum Acara Mahkamah Konstitusi dalam Teori dan Praktik - Sumadi, Ahmad Fadlil (Jurnal Konstitusi, 2011)
One of the important substance of Amendment of the Constitution of the Republic of Indonesia Year 1945 is the existence of the   Constitutional Court as a state institution that functions to handle certain cases in the field of state administration,  in  order  to  maintain  the  constitution  to be implemented in a responsible  manner in accordance with the will of  the people and democratic ideals. Constitutional Court’s constitutional authority to implement the principle of checks and balances which places all state agencies in the equivalent position so that there is a balance in  the administration of state The existence of the Constitutional Court is a real step to correct each other’s performance among state institutions. The Constitutional Court in carrying out justice to examine, hear and decide a case still refers to the organizing principle of judicial power which, among others, is carried out simply and quickly.